USING AUGMENTED REALITY BASED WORKSHEET IN LEARNING WRITING DESCRIPTIVE TEXT: VOCATIONAL HIGH SCHOOL STUDENTS’ VOICES - Andina Fitri Irawan; Yanuarti Apsari; Aseptiana Parmawati (Journal Of Educational Experts (JEE), 2026)
Conventional worksheets often do not provide engaging visual support. To address this issue, AR technology was integrated into the worksheet to help students visualize objects in 3D and interact with them during the learning process. This research explores students’ perspectives in using Augmented Reality (AR)-based worksheets to support descriptive writing. The study used a qualitative research method with interviews, observations, and questionnaires to understand students’ responses and learning experiences. Tenth-grade students from a vocational high school in Cimahi were involeved in this study. The findings reveal that AR-based worksheets made learning more interesting, motivated students to write, and helped them generate ideas more easily. Students reported that AR visuals allowed them to describe objects more accurately and confidently because they could see clear details such as colors, shapes, and dimensions. Despite some technical issues related to unstable internet access and scanning delays, the overall response was positive. Students also expressed interest in using AR for other English lessons in the future. In conclusion, AR-based worksheets offer meaningful support for descriptive writing, increase engagement, and serve as an innovative tool to improve learning quality in language classrooms.